The Psychometric Properties of the Persian Version of the Schizophrenia Caregiver Quality of Life Questionnaire - S Mokhtari; SA Haghayegh (Iran University of Medical Sciences, 2019)
Background & Aims: Schizophrenia is a severe psychological disorder, which adversely affects the life quality of the patients and their caregivers. The present study aimed to evaluate the psychometric properties of the Persian version of the schizophrenia caregiver quality of life questionnaire (S-CGQoL). Materials & Methods: This psychological study was conducted on all the caregivers of schizophrenia patients in Isfahan, Iran in 2018. In total, 200 caregivers of schizophrenia patients were selected via continuous sampling from three mental hospitals and three nursery centers during three months. Data were collected using the S-CGQoL by Richieri et al. (2011), which was translated in this study, and the World Health Organization (WHO) quality of life (WHOQOL) questionnaire by Skevington et al. (2004). In addition, 13 participants were selected to assess the retest reliability, and the reliability of the S-CGQoL was confirmed based on Cronbach's alpha. Results: The results of the conformational factorial analysis indicated significant correlations between the factorial load of all the items in the S-CGQoL with the related factor (P<0.05) with relatively appropriate efficiency indices. Moreover, the results of internal reliability indicated the Cronbach's alpha range of 0.54-0.92 in various sub-indices of the questionnaire. The results of the retest reliability showed that Pearson's correlation-coefficients for all the sub-indices of the S-CGQoL were significant in the two performed stages (P<0.05), with the overall correlation-coefficient of 0.96. In addition, the results of concurrent validity the sub-indices of the S-CGQoL with WHOQOL with the correlation-coefficient was 0.56. Therefore, the two scales had a potent, inverse association. Conclusion: According to the results, the Persian version of the S-CGQoL had proper validity and reliability and could be used for the caregivers of patients with schizophrenia in the healthcare centers in Iran.